2012
DOI: 10.2355/tetsutohagane.98.320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Martensite Fraction on Tensile Properties of Dual-Phase Steels

Abstract: Synopsis : Effects of martensite fraction on tensile properties and inhomogeneous deformation of microstructures in dual-phase steels have been investigated by TEM, SEM-EBSD and strain mapping using high-precision grid markers drawn by electron beam lithography. As is well known, when volume fraction of martensite is increased from 25% to 75%, yield and tensile strengths markedly increase while elongation decreases. It was found by EBSD that the average value of kernel average misorientation in ferrite increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Many experimental and analytical investigations were carried out to improve strain hardenability of steels. It has been reported that microstructural characteristics such as volume fraction and morphology of second phase and strength difference between soft and hard phases affect the tensile properties of dual-phase steels to a significant degree [5][6][7][8][9]. In the case of ferrite-bainite steel, it was reported that ferrite with 30-40% of bainite shows highest strain hardenability [7].…”
Section: Introductionmentioning
confidence: 97%
“…Many experimental and analytical investigations were carried out to improve strain hardenability of steels. It has been reported that microstructural characteristics such as volume fraction and morphology of second phase and strength difference between soft and hard phases affect the tensile properties of dual-phase steels to a significant degree [5][6][7][8][9]. In the case of ferrite-bainite steel, it was reported that ferrite with 30-40% of bainite shows highest strain hardenability [7].…”
Section: Introductionmentioning
confidence: 97%
“…Since the microstructures of DP steels are micro-scale mixtures of ferrite and martensite, mechanical interactions between the soft and hard phases must be clarified for fundamentally understanding their good mechanical properties. There are various microstructural parameters that can influence the deformation behavior of DP steels, namely, the volume fraction, size, hardness ratio, and distribution of the two phases [2][3][4][5][6][7]. In the present study, two different types of DP microstructures composed of soft ferrite and hard martensite are fabricated by different heat treatment routs in a low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hasegawa et al 6) recently investigated the relationship between the volume fraction of martensite and its mechanical properties in DP steels, and showed that the plastic strain of martensite increases with the increase in martensite fractions. Ueji et al 7) also showed that the groups of the laths in the martensite deformed nonuniformly under the plastic strain.…”
Section: Crystallographic Analysis Of Lath Martensite In Ferrite-martmentioning
confidence: 99%